1998
DOI: 10.1287/trsc.32.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Shortest Path Algorithms: An Evaluation Using Real Road Networks

Abstract: The classic problem of finding the shortest path over a network has been the target of many research efforts over the years. These research efforts have resulted in a number of different algorithms and a considerable amount of empirical findings with respect to performance. Unfortunately, prior research does not provide a clear direction for choosing an algorithm when one faces the problem of computing shortest paths on real road networks. Most of the computational testing on shortest path algorithms has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
185
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(190 citation statements)
references
References 15 publications
1
185
0
4
Order By: Relevance
“…Hence, at first glance, label-setting algorithms seem to be the better choice. However, several independent case studies [6,10,13,28,29,44,50,70] showed that SSSP implementations of label-correcting approaches frequently outperform labelsetting algorithms. Thus, worst-case analysis sometimes fails to bring out the advantages of algorithms that perform well in practice.…”
Section: Worst-case Versus Average-case Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, at first glance, label-setting algorithms seem to be the better choice. However, several independent case studies [6,10,13,28,29,44,50,70] showed that SSSP implementations of label-correcting approaches frequently outperform labelsetting algorithms. Thus, worst-case analysis sometimes fails to bring out the advantages of algorithms that perform well in practice.…”
Section: Worst-case Versus Average-case Analysismentioning
confidence: 99%
“…However, none of the alternative label-correcting algorithms succeeded to asymptotically improve on the O(n · m)-time worst-case bound of the simple BellmanFord approach. Still, a number of experimental studies [6,10,13,28,29,44,50,70] showed that some recent label-correcting approaches run considerably faster than the original Bellman-Ford algorithm and even outperform label-setting algorithms on certain data sets. So far, no profound average-case analysis has been given to explain the observed effects.…”
Section: Sequential Label-correcting Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our routing problem can be considered as the transpose of the one-to-some shortest path, since not all sensors are active simultaneously. A recent study by Zhan and Noon [33] suggested that the best approach for solving the one-to-some shortest path is Dijkstra's algorithm. In addition, Dijkstra's algorithm is shown to suit centralized routing [28].…”
Section: Routing Approachmentioning
confidence: 99%
“…In [3], authors evaluate 15 shortest path algorithms in real road networks of 10 states of the United Sates. They identify a set of recommendations regarding algorithm selection based on the computational performance.…”
Section: Introductionmentioning
confidence: 99%